Assessment of modified lignin cationic emulsifier for bitumen emulsions used in road paving. (5th October 2017) - Yuliestyan, A.; García-Morales, M.; Moreno, E.; Carrera, V.; Partal, P.
Abstract: The utilization of Kraft lignin as cationic emulsifier in the preparation of bitumen emulsions has been assessed in this work. Thus, Kraft lignin was previously modified in alkaline medium in presence of tetraethylene pentamine (TEPA) and formaldehyde, according to the Mannich reaction. Solubility in water phase as a function of pH demonstrated the amphoteric nature of the reaction product, which enables its potential application in cationic bitumen emulsions. Bitumen emulsions stabilized by modified Kraft lignin (MKL) were further studied. Different B/W ratios, which mainly affected the high-shear-rate-limiting viscosities, yielded more similar mean droplet diameters than different pHs, whose effect on viscosity was mainly at low shear rates. Moreover, viscous flow and linear viscoelasticity tests revealed enhanced rheological performance of the MKL bitumen residue if compared to the parent base bitumen. Finally, half warm mix asphalt (HWMA) specimens containing reclaimed asphalt pavement (RAP) were studied, and the results compared with those corresponding to virgin aggregate. In both cases, the preparation of HWMA with a selected 60/40 MKL bitumen emulsion at 80 °C by gyratory compaction was successful. Compared to the virgin aggregate, the specimen derived from 100% RAP showed much higher mechanical resistance due to a partial blending of fresh binder with RAP aged binder. Graphical abstract: Highlights: Modified lignin emulsifier soluble at pH between 1-5 for cationic application Microstructural changes beyond 2 wt.% emulsifier yielded bitumen residue with improved flow viscous and viscoelastic properties Half warm mix asphalt with 100% RAP successfully prepared using bitumen emulsion containing modified lignin